Determinación de la presencia de Helicobacter pylori mediante un dispositivo cromatográfico específico, en cerdos sacrificados en el Frigorífico Vijagual. - Gonzalez Gomez, Ana; Rodriguez Suarez, Elena; Gomez Celis, Joaquin (Spei Domus, 2005)
Pathologies of uncertain etiology manifested by gastric ulcers have been observed in pig. This research paper shows the association of Helicobacter sp. as the main causing agent of this disorder by studying a sample of 100 pigs slaughtered at the Vijagual abattoir in the Bucaramanga city. Sera samples were analyzed and samples of gastric tissue were processed by histopathological methods using Hematoxiline-Eosine and Warthin-Starry to confirm the correlation between spiral bacteria and gastric lesions. Blood sera of positive pigs in the histopathological examination were examined by a specific chromatographic device or immunoassay (ACON ®). Analysis of results was based on a experimental model describing the number of positive and negative pigs to Helicobacter sp. bacteria. Histopathologically, 53% of the animals were positive and 47% were negative. The species of bacteria assosiated were Helicobacter pylori (60,3%) and Helicobacter hellmanii (39,6%). For the serological procedure, 25 positive and 25 negative samples to Helicobacter sp. were analyzed. A reliability of 92% with the specific test and 75% of negative confirmation was found. The statistical test of Chi Square was utilized to evaluate the association of Helicobacter sp. to gastric lesions. Standardization was carried out by the ACON ®specific chromatographic device. This test is designed for the detection of IgG antibodies against Helicobacter pylori in human serum for the diagnosis of gastrointestinal diseases. Based on this method, reliability and specificity of the test was demonstrated for the determination of Helicobacter pylori in sera of pigs with gastric lesions. This technique represents a precise aid for the management of gastric clinical malfunctions that are frequentin porcine exploitations nowadays.